2013
DOI: 10.1049/iet-its.2011.0188
|View full text |Cite
|
Sign up to set email alerts
|

Effective traffic management based on bounded rationality and indifference bands

Abstract: Constrained cognitive abilities cause imperfections in drivers' choice behaviour and appear largely systematic and predictable. This study introduces the concept of 'effective control space' to build upon this knowledge as an opportunity to increase the effectiveness of Dynamic Traffic Management (DTM). Within the control space boundaries it is assumed that drivers do not act upon the effects of DTM measures, they behave as being indifferent to them. This study debates that: (i) drivers' ability to detect chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 33 publications
(62 reference statements)
0
18
0
Order By: Relevance
“…It is argued that this 'range of inattention' along the demand curve gives retailers an incentive for small price increments to increase profit [8]. Analogically and as conceptualised and demonstrated in earlier work by the authors [9,10], when applied in the context of transport thresholds may give policy makers, road operators and traffic engineers an incentive 'lever' to modify choice attributes, which in turn will increase the performance of the traffic system.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It is argued that this 'range of inattention' along the demand curve gives retailers an incentive for small price increments to increase profit [8]. Analogically and as conceptualised and demonstrated in earlier work by the authors [9,10], when applied in the context of transport thresholds may give policy makers, road operators and traffic engineers an incentive 'lever' to modify choice attributes, which in turn will increase the performance of the traffic system.…”
mentioning
confidence: 86%
“…The aforementioned findings offer an illustration of the size of thresholds under different circumstances. Examples of their application are given in [9,10] which showed a reduction in total travel time of 5% compared to user equilibrium in case of an threshold of 4 minutes for a trip of approximately 22 minutes. Additionally, the improvement in the network performance increased with an increasing threholds, up to 14% in case of a threshold of 10 minutes.…”
Section: Main Findingsmentioning
confidence: 99%
“…This perspective of individual decision making is known as bounded rationality and contributes to the indifference band (IB). On the basis of a simple example, using the green split of traffic lights as control mechanism, it was already demonstrated that the application of IBs can successfully steer a system towards its optimal state [8]. This paper therefore proposes the use of these psychological constructs to improve the network performance, in such a way that the user interests remain respected.…”
Section: Introductionmentioning
confidence: 99%
“…Using this knowledge on human imperfection and bounded rationality provides opportunities for the effective operation of traffic network management as stated by the concept of 'regulation flexibility' [6]. This concept tries to take advantage of traveler's (in)ability to respond to some change in the attributes of their trip or the traffic system, in contrast to the many research that aims to compensate for people's failure to detect changes as a result of change blindness [7,8].…”
mentioning
confidence: 99%
“…In this paper, the decision-making process is regarded as a process consisting of three successive stages: 'observation', 'evaluation' and 'choice'. A conceptual framework is discussed in [6], which illustrates how perceptual factors influence the three stages and lead to regulation flexibility and traffic management measures. This paper focuses on observation and evaluation.…”
mentioning
confidence: 99%